2009
DOI: 10.1111/j.1600-0706.2009.17392.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential virulence in a multiple‐host parasite of bumble bees: resolving the paradox of parasite survival?

Abstract: Parasite virulence determines both the impact that parasites have on their hosts and parasite fitness. While most studies of virulence have involved single-species hostÁparasite interactions, the majority of parasites are likely to use multiple concurrent host species. Our understanding of how this impacts on parasite epidemiology and virulence is limited. Using the bumble bee Bombus lucorum, which exists in sympatry with B. terrestris in multi-species assemblages, and their generalist micosporidian parasite N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
(85 reference statements)
0
59
0
Order By: Relevance
“…Spores of Nosema bombi from Bombus terrestris were less infective in Bombus lapidarius and Bombus hypnorum, but even genotype-genotype interaction were present, since N. bombi showed different infectivity in different B. terrestris colonies (Schmid-Hempel and Loosli, 1998). Also the virulence of N. bombi was different in B. terrestris and Bombus lucorum, possibly a consequence of the shorter life cycle of B. lucorum (Rutrecht and Brown, 2009). It is evident, to resolve these issues for spiroplasmas, more research is needed, for now we know from feeding experiments in honeybees these bacteria can cause harm in pollinators (Clark, 1978;Mouches et al, 1982).…”
Section: Resultsmentioning
confidence: 88%
“…Spores of Nosema bombi from Bombus terrestris were less infective in Bombus lapidarius and Bombus hypnorum, but even genotype-genotype interaction were present, since N. bombi showed different infectivity in different B. terrestris colonies (Schmid-Hempel and Loosli, 1998). Also the virulence of N. bombi was different in B. terrestris and Bombus lucorum, possibly a consequence of the shorter life cycle of B. lucorum (Rutrecht and Brown, 2009). It is evident, to resolve these issues for spiroplasmas, more research is needed, for now we know from feeding experiments in honeybees these bacteria can cause harm in pollinators (Clark, 1978;Mouches et al, 1982).…”
Section: Resultsmentioning
confidence: 88%
“…and may play key ecological roles in the population dynamics of their hosts, which are among the most important pollinators globally in both agriculturally intense settings (Velthuis and Van Doorn, 2006) and in natural settings where they are cornerstone species in pollination networks (Memmott et al, 2004). Most of these studies have been conducted in Western Europe and have focused on the most common host species, Bombus terrestris L. and Bombus lucorum L. (Shykoff and SchmidHempel, 1991;Korner and Schmid-Hempel, 2005;Rutrecht and Brown, 2009). Little is known about the pathogen complex of the approximately 52 North American Bombus species.…”
Section: Introductionmentioning
confidence: 98%
“…N. bombi is an obligate intracellular pathogen that produces systemic disease in its host (Fries et al, 2001;Larsson, 2007); the effects are generally chronic, including reduction in individual reproduction rate Schmid-Hempel, 2007, 2008), life span (Fantham and Porter, 1914;Schmid-Hempel and Loosli, 1998;Rutrecht and Brown, 2009) and colony growth (Rutrecht and Brown, 2009). There has been a limited amount of research on susceptibility of European bumble bee species to N. bombi (Schmid-Hempel and Loosli, 1998;Schmid-Hempel, 2007, 2008;Rutrecht and Brown, 2009), and none for American bumble bees. One European study found significant differences in susceptibility of different host species to N. bombi spores harvested from B. terrestris (Schmid-Hempel and Loosli, 1998), but Rutrecht et al (2007) reanalyzed these data and did not find differences.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, the multi-host microsporidian Nosema bombi appears to exhibit runaway virulence in one host species Otti & Schmid-Hempel (2008) and more adaptive virulence in a second (Rutrecht & Brown 2009). This pattern may match predictions based on host resistance Gandon (2004), but the relationship to host quality is unclear.…”
Section: Host Assemblages: From Theory To Incomplete Empirical Studiesmentioning
confidence: 99%